AB1099 Outcome of Undifferentiated Arthritis- A Study of 154 Patients. (10th June 2014) - Rodríguez-Muguruza, S.; Martinez-Morillo, M.; Olive, A.; Riveros-Frutos, A.; Sanint, J.; Prior, A.; Holgado, S.; Mateo, L.; Cañellas, G.; Tena, X.
Abstract : Background: Undifferentiated arthritis (UA) is defined as an inflammatory arthritis in which no definitive diagnosis can be made. The prognosis of patients with UA may vary from spontaneous remission, to severe defined inflammatory joint disease. Patients UA poses a challenging problem to the rheumatologist. It is important to identify patients who will develop a persistent and/or erosive disease because early treatment might offer an effective means to slow disease progression. Objectives: To describe the outcome of patients with UA after 30 months of follow up. Methods: Design retrospective (2006 - 2011) in an academic tertiary hospital with a reference area of 850, 000 inhabitants. We reviewed the medical records of patients with "undifferentiated arthritis" from the database of rheumatology Department. We reviewed the pattern of involvement at the onset of the disease and final diagnosis in December 2013. Results: A hundred and fifty four patients were included. The involvement, at the beginning of the disease was: 36 (23.3%) monoarticular, 71 (46.1%) oligoarticular and 47 (30.5%) polyarticular. During follow-up, it was observed that 30 (19.5%) patients went into remission spontaneously, 57 (64.9%) evolved to a defined inflammatory joint disease and 67 (43.5%) continued under the diagnosis of undifferentiated arthritis. Among those patients were a definite inflammatory joint disease was established: 38 (66.6%) continued follow up controls, 16 (28%) discontinued the follow-up and 3 (5.3%) were discharged. A progression to extended polyarthitis was observed in 3 patients with an oligoarticular pattern. Four patients with monoarthitis developed oligoarthritis. The knee was the most commonly involved joint (58.3%). Conclusions: The most common pattern of joint involvement in UA is oligoarticular. Furthermore half of patients with UA went into remission. Patients with a monoarticular pattern had a greater chance of spontaneous remission compared with patients with oligo and polyarticular involvement. The frequency of follow up was also significantly higher in patients with definite inflammatory joint disease compared with patients with persistent UA (66.6% versus 47.7%). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2933